Workshop of Terravor: Terrarium as An Education Media for Introducing Carnivorous Plants of Sumatra to the Society of Nature Themed Art Lovers - Stia Prihatiningsih Idris; Atthoriq Fauzan; Amanda Rahmiati,; Dwi Suci Mahesa Putri; Mellanie Alia Putri; Muhammad Idris (Warta Pengabdian Andalas, 2024)
There are still many plant species that the public currently needs to be made aware. It is because the uses of plants still need to be well explored, which has left them with little practical usefulness. The potential of these plants can be utilized as a tool in educational media and as items with creative and unique value in the commercial sector. Carnivorous plants are among them. In addition to having unique shapes, art enthusiasts can use this plant to turn their interests and skills into terrarium products. TERRAVOR is an innovative terrarium product with carnivorous plants as the main ingredient. This product specializes in carnivorous plants found in the Sumatra region to educate the public regarding the sustainable use of these plants and their status in nature so that the use value of these plants can be maintained for an extended period. This workshop aims to educate the public, especially a society of nature-themed art lovers, about the sustainable use of carnivorous plants. This one-day workshop involved a society interested in terrarium techniques and the uniqueness of carnivorous plants. In this workshop, participants consisting of 13 people who have natural-themed artistic talent were introduced to the ins and outs of carnivorous plants, their conservation status, how to cultivate them in terrarium conditions, and their care. The results of this workshop showed that the number of participants' understanding of the importance of carnivorous plants increased. In addition, participants know more about how to use it sustainably without destroying its natural populations.